Spatial approach of pluriactivity in african rural area. Little jobs and big works in Coastal Guinea - (:unkn) unknown (My University, 2007)
Based upon a two years applied research program in Coastal Guinea, our thesis aims at refreshing classical approaches of rural Africa in order to give a new light on development policies. Today, the regular agrarian entry is not adapted to describing rural life in Africa, further more to devising programs aiming at improving the life of local populations. Agriculture keeps a structuring part, but has to be viewed in the light of the numerous other activities, which are invigorated by the ever increasing role of money in trade. Pluriactivity has been analysed through quantitative approaches based upon households and individuals. It enabled us to substitute “systems of activities” to “rural systems”, both semantically and theoretically. The complexity of pluriactivity combinations has been asserted through time allocation, work organisation, and task patterns. Our work shows that these numerous combinations draw, at different scales, territories of action pertinent for the searcher as well as the decision maker.
Keywords: African Research